Knock-Down of the Phosphoserine Phosphatase Gene Effects Rather N- Than S-Metabolism in Arabidopsis thaliana - Samuilov, Sladjana; Rademacher, Nadine; Brilhaus, Dominik; Flachbart, Samantha; Arab, Leila; Kopriva, Stanislav; Weber, Andreas P. M.; Mettler-Altmann, Tabea; Rennenberg, Heinz (Frontiers in Plant Science, 2018)
The aim of present study was to elucidate the significance of the phosphorylated pathway of Ser production for Cys biosynthesis in leaves at day and night and upon cadmium (Cd) exposure. For this purpose, Arabidopsis wildtype plants as control and its psp mutant knocked-down in phosphoserine phosphatase (PSP) were used to test if (i) photorespiratory Ser is the dominant precursor of Cys synthesis in autotrophic tissue in the light, (ii) the phosphorylated pathway of Ser production can take over Ser biosynthesis in leaves at night, and (iii) Cd exposure stimulates Cys and glutathione (GSH) biosynthesis and effects the crosstalk of S and N metabolism, irrespective of the Ser source. Glycine (Gly) and Ser contents were not affected by reduction of the psp transcript level confirming that the photorespiratory pathway is the main route of Ser synthesis. The reduction of the PSP transcript level in the mutant did not affect day/night regulation of sulfur fluxes while day/night fluctuation of sulfur metabolite amounts were no longer observed, presumably due to slower turnover of sulfur metabolites in the mutant. Enhanced contents of non-protein thiols in both genotypes and of GSH only in the psp mutant were observed upon Cd treatment. Mutation of the phosphorylated pathway of Ser biosynthesis caused an accumulation of alanine, aspartate, lysine and a decrease of branched-chain amino acids. Knock-down of the PSP gene induced additional defense mechanisms against Cd toxicity that differ from those of WT plants.